2016
DOI: 10.1371/journal.pone.0147001
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery Combined with Regenerative Biomaterials in Treating Intra-Bony Defects: A Meta-Analysis

Abstract: BackgroundWith the popularity of minimally invasive surgery (MIS) in periodontics, numerous publications have evaluated the benefits of MIS with or without various regenerative biomaterials in the treatment of periodontal intra-bony defects. However, it is unclear if it is necessary to use biomaterials in MIS. Thus, we conducted a meta-analysis of randomized clinical trials in patients with intra-bony defects to compare the clinical outcomes of MIS with regenerative biomaterials for MIS alone.MethodsThe author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 38 publications
(71 reference statements)
2
27
0
1
Order By: Relevance
“…In thirteen studies of this systematic review, no biomaterials or biologic agents were used in at least one analysed group. The use of biomaterials or membranes does not seem to contribute to the improvement of clinical periodontal parameters after a minimally invasive periodontal surgery (Cortellini & Tonetti, ; Liu, Hu, Zhang, Li, & Song, ). This is not true for the traditional periodontal surgery, since the absence of a regenerative material has a significant impact on the effectiveness of these surgical procedures (Needlemann et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In thirteen studies of this systematic review, no biomaterials or biologic agents were used in at least one analysed group. The use of biomaterials or membranes does not seem to contribute to the improvement of clinical periodontal parameters after a minimally invasive periodontal surgery (Cortellini & Tonetti, ; Liu, Hu, Zhang, Li, & Song, ). This is not true for the traditional periodontal surgery, since the absence of a regenerative material has a significant impact on the effectiveness of these surgical procedures (Needlemann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The precise management of the surgical site, obtained by the use of magnification instruments, could facilitate clot stability and maturation, good flap perfusion and space maintenance (Cortellini et al, ; Trombelli et al, ). These intrinsic aspects of MIPS may also explain why a substantial amount of PPD reduction and CAL gain can be achieved even when the use of biomaterials or membranes is not associated with minimally invasive approaches (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…(Cortellini & Tonetti, 2011;Schincaglia, Hebert, Farina, Simonelli, & Trombelli, 2015). In this context, it is important to highlight how studies have consistently shown no differences in clinical and radiographic outcomes when GTR (Trombelli, Simonelli, Pramstraller, Wikesjo, & Farina, 2010) or EMD (Cortellini & Tonetti, 2011) was used as adjunct to minimally invasive surgeries, as observed in a recent meta-analysis (Liu, Hu, Zhang, Li, & Song, 2016).…”
Section: Comparisons Between Ofd and Regenerative Proceduresmentioning
confidence: 94%
“…19,20 Cortellini and Tonetti (2007) in their case cohort study involving 13 intrabony defects inferred that MIST along with enamel matrix derivative resulted in gain in clinical attachment level and gain in the bone fill with limited patient morbidity. 21 In a meta-analysis conducted by Liu et al (2016), there were no statistically significant difference regarding clinical attachment level gain and probing pocket depth reduction, gain in the recession levels and radiographic bone fill between the MIS plus biomaterials group and the MIS group alone indicating that it is important to take costs and benefits into consideration while making a decision about therapeutic approach. 22 Advantages of MIST:…”
Section: Discussionmentioning
confidence: 99%